Physician survey to determine how dengue is diagnosed, treated and reported in puerto rico. - Kay M Tomashek; Brad J Biggerstaff; Mary M Ramos; Carmen L Pérez-Guerra; Enid J Garcia Rivera; Wellington Sun (Public Library of Science (PLoS), 2014)
Dengue is a major cause of morbidity in Puerto Rico and is well-known to its physicians. Early case identification and timely initiation of treatment for patients with severe dengue can reduce medical complications and mortality. To determine clinical management and reporting practices, and assess knowledge of dengue and its management, a survey was sent to 2,512 physicians with a medical license in Puerto Rico. Of the 2,313 physicians who received the survey, 817 (35%) completed the questionnaire. Of the respondents, 708 were currently practicing medicine; 138 were board certified (Group 1), 282 were board eligible (Group 2), and 288 had not finished residency (Group 3). Although respondents clinically diagnosed, on average, 12 cases of dengue in the preceding three months, 31% did not report any suspected cases to public health officials while about half (56%) reported all cases. Overall, 29% of respondents correctly identified early signs of shock and 48% identified severe abdominal pain and persistent vomiting as warning signs for severe dengue with the proportion of correct respondents highest in Group 1. Reportedly about sixty percent (57%) appropriately never give corticosteroids or prophylactic platelet transfusions to dengue patients. One third (30%) of respondents correctly identified administration of intravenous colloid solution as the best treatment option for dengue patients with refractory shock and elevated hematocrit after an initial trial of intravenous crystalloids, and nearly one half (46%) correctly identified administration of a blood transfusion as the best option for dengue patients with refractory shock and decreased hematocrit after a trial of intravenous crystalloids. Even though dengue has been endemic in Puerto Rico for nearly 4 decades, knowledge of dengue management is still limited, compliance with WHO treatment guidelines is suboptimal, and underreporting is significant. These findings were used to design a post graduate training course to improve the clinical management of dengue.